On the triggering mechanism of Heinrich events - Álvarez Solas, Jorge; Ramstein, Gilles (Proceedings of the National Academy of Sciences, 2011)
We thank A. Robinson and E. E. Lucio-Eceiza for comments, helpful discussions, and artistic assistance. This work was performed under the Spanish program of the International Campus of Excellence. Spanish program of the International Campus of Excellence Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub